Maternal Diabetes-Induced Suppression of Oxytocin Receptor Contributes to Social Deficits in Offspring - Liu, Jianbo; Liang, Yujie; Jiang, Xing; Xu, Jianchang; Sun, Yumeng; Wang, Zichen; Lin, Ling; Niu, Yanbin; Song, Shiqi; Zhang, Huawei; Xue, Zhenpeng; Lu, Jianping; et al. (Frontiers in Neuroscience, 2021)
Autism spectrum disorders (ASD) are a group of neurodevelopmental disorders characterized by impaired skills in social interaction and communication in addition to restricted and repetitive behaviors. Many different factors may contribute to ASD development; in particular, oxytocin receptor (OXTR) deficiency has been reported to be associated with ASD, although the detailed mechanism has remained largely unknown. Epidemiological study has shown that maternal diabetes is associated with ASD development. In this study, we aim to investigate the potential role of OXTR on maternal diabetes-mediated social deficits in offspring. Our in vitro study of human neuron progenitor cells showed that hyperglycemia induces OXTR suppression and that this suppression remains during subsequent normoglycemia. Further investigation showed that OXTR suppression is due to hyperglycemia-induced persistent oxidative stress and epigenetic methylation in addition to the subsequent dissociation of estrogen receptor β (ERβ) from the OXTR promoter. Furthermore, our in vivo mouse study showed that maternal diabetes induces OXTR suppression; prenatal OXTR deficiency mimics and potentiates maternal diabetes-mediated anxiety-like behaviors, while there is less of an effect on autism-like behaviors. Additionally, postnatal infusion of OXTR partly, while infusion of ERβ completely, reverses maternal diabetes-induced social deficits. We conclude that OXTR may be an important factor for ASD development and that maternal diabetes-induced suppression of oxytocin receptor contributes to social deficits in offspring.